The Relationship Between Multiple Role Conflict, Work Expense and Work Stress on The Performance of Women Employees - Ria Zulfiana; Budiyono Pristyadi; Ahmad Qoni Dewantoro; Alkusani Alkusani; Asep Saepuloh (Universitas Muhammadiyah Gresik, 2021)
This study aims to determine the effect of multiple role conflicts, workload and work stress on the performance of female employees of the production division of PT Madsumaya Indo Seafood. Using a method is a sampling technique when all members of the population are used as samples. The number of samples used in this study were 68 respondents. The analysis technique for testing hypotheses uses the Statistical Package for the Social Sciences (SPSS). The Technique analysis data used multiple regression linear analysis. The results of this study indicate that partially multiple role conflict variables do not have a negative effect on the performance of female employees in the production division of PT M adsumaya Indo Seafood, while workload and work stress have a negative effect on the performance of female employees in the production division of PT Madsumaya IndoSeafood.